2022
DOI: 10.1186/s40468-021-00152-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictability of IELTS in a high-stakes context: a mixed methods study of Chinese students’ perspectives on test preparation

Abstract: High-stakes language tests are used around the world as a gatekeeping tool under the internationalization of higher education. However, the predictable aspect of the high-stakes language tests is seldom discussed, especially from students’ perspectives. This study aims to address this gap by aiming to better understand how certain factors and conditions contribute to the predictability issue of IELTS from students’ perspectives within a high-stakes context. This study used a mixed method approach to investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 21 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Although both types of scoring systems they are both different, yet they are related in many ways as it has been indicated in some studies (Cho & Bridgeman, 2012;Ginther & Yan, 2018;Rahmat et al, 2015) The TOEFL or Test of English as a Foreign Language score is used to measure a person's mastery of the English language (Sawaki & Sinharay, 2018). It is an exam taken mainly by people whose native language is not English, and is generally required for entrance into universities in English-speaking countries, as well as for many internships and employment opportunities (Dang & Dang, 2021;Kokhan, 2013;Liao, 2022bLiao, , 2022cMa & Chong, 2022). The TOEFL score is based solely on the performance on timed tests Teachers' scores, on the other hand, typically reflect a variety of methods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although both types of scoring systems they are both different, yet they are related in many ways as it has been indicated in some studies (Cho & Bridgeman, 2012;Ginther & Yan, 2018;Rahmat et al, 2015) The TOEFL or Test of English as a Foreign Language score is used to measure a person's mastery of the English language (Sawaki & Sinharay, 2018). It is an exam taken mainly by people whose native language is not English, and is generally required for entrance into universities in English-speaking countries, as well as for many internships and employment opportunities (Dang & Dang, 2021;Kokhan, 2013;Liao, 2022bLiao, , 2022cMa & Chong, 2022). The TOEFL score is based solely on the performance on timed tests Teachers' scores, on the other hand, typically reflect a variety of methods.…”
Section: Discussionmentioning
confidence: 99%
“…The use of standardized tests an initial English test is also mentioned in Ma and Chong (2022) and Liao(2022). In Ma and Chong (2022) IELTS was used to determine whether students are eligible to continue studying at the EMI programme or not. In Liao(2022), SAT was employed to place students into EFL class which is not the case of the current study.…”
Section: Hutabaratmentioning
confidence: 99%
See 1 more Smart Citation
“…The writing section of the IELTS exam is notorious for its lower scores, but the author employed various strategies to achieve a high score in this section [4]. Firstly, they studied standard answers from practice tests to understand the appropriate format and language structure.…”
Section: Writing Sectionmentioning
confidence: 99%
“…Research also revealed the negative impact of TP. TP can have a negative impact on students by restricting their English learning scope, forcing them to self-isolated learning, taking repeated tests, and purchasing predicted answers (Ma & Chong, 2022). Additionally, sellers of predicted answers are thought to be engaged in unethical practices since doing such test-taking strategies can help students achieve a score higher than their language proficiency may warrant (Hu & Trenkic, 2021).…”
Section: Introductionmentioning
confidence: 99%